Cytokine‐induced megakaryocytic differentiation is regulated by genome‐wide loss of a uSTAT transcriptional program. (23rd December 2015) - Park, Hyun Jung; Li, Juan; Hannah, Rebecca; Biddie, Simon; Leal‐Cervantes, Ana I; Kirschner, Kristina; Flores Santa Cruz, David; Sexl, Veronika; Göttgens, Berthold; Green, Anthony R
Abstract: Metazoan development is regulated by transcriptional networks, which must respond to extracellular cues including cytokines. The JAK/STAT pathway is a highly conserved regulatory module, activated by many cytokines, in which tyrosine‐phosphorylated STATs (pSTATs) function as transcription factors. However, the mechanisms by which STAT activation modulates lineage‐affiliated transcriptional programs are unclear. We demonstrate that in the absence of thrombopoietin (TPO), tyrosine‐unphosphorylated STAT5 (uSTAT5) is present in the nucleus where it colocalizes with CTCF and represses a megakaryocytic transcriptional program. TPO‐mediated phosphorylation of STAT5 triggers its genome‐wide relocation to STAT consensus sites with two distinct transcriptional consequences, loss of a uSTAT5 program that restrains megakaryocytic differentiation and activation of a canonical pSTAT5‐driven program which includes regulators of apoptosis and proliferation. Transcriptional repression by uSTAT5 reflects restricted access of the megakaryocytic transcription factor ERG to target genes. These results identify a previously unrecognized mechanism of cytokine‐mediated differentiation. Synopsis: In the unphosphorylated state, STAT5 represses a transcription program that restrains megakaryocyte differentiation. Cytokine‐induced STAT5 tyrosine phosphorylation triggers genome‐wide relocation to STAT consensus sites, including regulators of apoptosis and proliferation. uSTAT5 binds to chromatin, colocalizes with CTCF, and represses a poised megakaryocytic transcriptional program. TPO triggers genome‐wide redistribution of STAT5 and alleviates the repression of uSTAT5 target genes. uSTAT5 functions as a molecular switch by restricting access of the megakaryocytic transcription factor ERG to target genes. Abstract : In the unphosphorylated state, STAT5 represses a transcription program that restrains megakaryocyte differentiation. Cytokine‐induced STAT5 tyrosine phosphorylation triggers genome‐wide relocation to STAT consensus sites, including regulators of apoptosis and proliferation.